Wyoming proud - Palmer, Diana (Palmer, Diana. Wyoming men series, 2023)
"It takes one night for Erianne Mitchell to fall heart-first for dashing architect Ty Mosby. They work together and have friends in common--and a searing attraction that seems far too good to last. But when a devastating mistake tears them apart, Erianne flees to Wyoming with a secret, one she hopes Ty never discovers. She did nothing wrong, and she'll never ask Ty to forgive her. She'll support herself...and the baby growing inside her. How can she be with a man who doesn't trust her? Ty knows exactly what he's lost and he'll do anything to beg for her forgiveness and win back her trust. When he finds her, she's just as proud as he remembers. Is it too late for him to make amends...or is destiny about to test them in an even bigger way?"